2019
DOI: 10.1371/journal.pone.0223025
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota of MR1 deficient mice confer resistance against Clostridium difficile infection

Abstract: Clostridium difficile (Cd) infection (CDI) typically occurs after antibiotic usage perturbs the gut microbiota. Mucosa-associated invariant T cells (MAIT) are found in the gut and their development is dependent on Major histocompatibility complex-related protein 1 (MR1) and the host microbiome. Here we were interested in determining whether the absence of MR1 impacts resistance to CDI. To this end, wild-type (WT) and MR1-/- mice were treated with antibiotics and then infected with Cd spores. Surprisingly, MR1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 43 publications
4
24
0
Order By: Relevance
“…It has been reported that exposure to Cef via drinking water disrupts the gut microbiota of mice, decreases bacterial load by three orders of magnitude, and alters community composition [24]. Our previous study showed that the stool microbiota of MR1 −/− mice were minimally perturbed by Cef treatment when compared with WT mice [12]. In order to investigate whether antibiotic-induced changes in BA metabolism follow a similar pattern, the total BA intensity levels in cecal content and stool samples from both KO and WT mice were measured and compared.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been reported that exposure to Cef via drinking water disrupts the gut microbiota of mice, decreases bacterial load by three orders of magnitude, and alters community composition [24]. Our previous study showed that the stool microbiota of MR1 −/− mice were minimally perturbed by Cef treatment when compared with WT mice [12]. In order to investigate whether antibiotic-induced changes in BA metabolism follow a similar pattern, the total BA intensity levels in cecal content and stool samples from both KO and WT mice were measured and compared.…”
Section: Discussionmentioning
confidence: 96%
“…MR1 and bacterial derived riboflavin derivatives are required for the activation of MAIT cells, which conduct antimicrobial activity. Our previous study [11,12] showed that MR1 −/− mice had inherent differences in microbial composition when compared to WT mice both before and after Cef exposure. Surprisingly, MR1 −/− mice exhibited resistance to CDI, which can be transferrable when the microbiome of MR1 −/− mice is transferred to WT mice via fecal microbiota transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we treated recipient mice with broad spectrum antibiotics (poorly absorbed) for 1 week to reduce intestinal bacterial load prior to fecal transplantation. A number of studies have used this approach to assess the functional effects of microbiota/fecal transplants . Although other studies have used germ‐free mice as recipient of fecal transplants, we opted to use the antibiotic depletion approach to overcome the dysregulated immune system in the germ‐free mice.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have used this approach to assess the functional effects of microbiota/fecal transplants. (115)(116)(117) Although other studies have used germ-free mice as recipient of fecal transplants, we opted to use the antibiotic depletion approach to overcome the dysregulated immune system in the germ-free mice.…”
Section: Discussionmentioning
confidence: 99%